Pengaruh Pemberian Kredit Simpan Pinjam Dan Perputaran Likuiditas Terhadap Pendapatan Koperasi Kredit Syurdikara - Damianus Tola; Irmawati Ahmad (Program Studi Pendidikan Ekonomi, Universitas Flores, 2017)
This research is goal to know: 1). Know the lending to the income of the cooperative syuradikara 2). know the cycles of liquditas the increase in the income of the syuradikara unions. The research method used descriptive quantitative and descriptive qualitative, Types of data collected secondary data with the size of Current Ratio. Current Ratio is the ratio between the amount of current assets with current debt. Analyzer used to know the effect of credit saving and leverage and liquidity turnover to unions income at credit cooperative Syurdikara using Multiple Regression Analysis. There is a significant effect of lending and liquidity turnover on the earnings of credit unions Syurdikara. Because the value of F count for -26.8, is smaller than 0.19. This means there are other factors affecting Syurdikara cooperative income.